2020
DOI: 10.1186/s12935-019-1073-x
|View full text |Cite
|
Sign up to set email alerts
|

LINC00908 negatively regulates microRNA-483-5p to increase TSPYL5 expression and inhibit the development of prostate cancer

Abstract: Background: Accumulating evidence has associated aberrant long non-coding RNAs (lncRNAs) with various human cancers. This study aimed to explore the role of LINC00908 in prostate cancer (PCa) and its possible underlying mechanisms. Methods: Microarray data associated with PCa were obtained from the Gene Expression Omnibus (GEO) to screen the differentially expressed genes or lncRNAs. Then, the expression of LINC00908 in PCa tissues and cell lines was detected by reverse transcription-quantitative polymerase ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 33 publications
0
9
0
Order By: Relevance
“… 7 Nevertheless, Fan et al found that LINC00908 inhibited prostate cancer progression by negatively regulating microRNA-483-5p and then elevate the expression of TSPYL5. 5 Obviously, the biological roles and mechanism of LINC00908 in human diseases including DLBCL are largely unknown. The current study aimed to investigate the exact roles and potential mechanism of LINC00908 in DLBCL.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 7 Nevertheless, Fan et al found that LINC00908 inhibited prostate cancer progression by negatively regulating microRNA-483-5p and then elevate the expression of TSPYL5. 5 Obviously, the biological roles and mechanism of LINC00908 in human diseases including DLBCL are largely unknown. The current study aimed to investigate the exact roles and potential mechanism of LINC00908 in DLBCL.…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that LINC00908 inhibited prostate cancer progression. 5 Nevertheless, other studies reported the oncogenic role of LINC00908 in hepatocellular carcinoma and colorectal cancer. 6 , 7 Obviously, the biological effects and underlying mechanism of LINC00908 in the development of main human malignant diseases, including DLBCL, remain elusive.…”
Section: Introductionmentioning
confidence: 99%
“…Linc00908 had been reported to be highly expressed in liver cancer and to interact with SOX4, thereby increasing its stability by inhibiting proteasomal degradation [42]. Linc00908 sponges with miR-483-5p in prostate cancer, and competitively reduces miR-483-5p targeting to TSPYL5 (testis-specific Y-encoded-like protein 5) to exert its anticancer function [43]. A recent study reported on a small 60 aa regulatory micropeptide of STAT3 (ASPRS) encoded by linc00908 in patients with triple negative breast cancer (TNBC) (Fig.…”
Section: Asprsmentioning
confidence: 99%
“…In recent years, emerging research has revealed that lncRNAs are crucial players in the occurrence and progression of diverse malignancies including PCa 7–8 . For example, LINC00908 expression is down‐regulated in PCa and inhibits the development of PCa 9 . lncRNA ZFAS1 and lncRNA UCA1 expression are up‐regulated in PCa, and they facilitate the growth and metastasis of PCa cells 10,11 .…”
Section: Introductionmentioning
confidence: 99%
“…development of PCa. 9 lncRNA ZFAS1 and lncRNA UCA1 expression are up-regulated in PCa, and they facilitate the growth and metastasis of PCa cells. 10,11 lncRNA small nucleolar RNA host gene 8 (SNHG8) plays an important role in promoting tumor growth and metastasis in esophageal squamous cell carcinoma, colorectal cancer and pancreatic cancer.…”
mentioning
confidence: 99%